Knowledge attitudes , practices and satisfaction of patients towards drugs - presecribed at medical clinic of the national hospital of Sri Lanka - Talagala, D.C.S (My University, 2003)
This descriptive study was carried out with the objective of assesing the knowledge, attitudes and practices of patients attendingthe medical clinic of National hospital in Sri Lanka ,on drugs-prescribed to them and thir satisfaction on prescribing and dispending of drugs.The finding of this study call for more focus in providing patients with basic information on drugs -prescribed to them,with much attention on the patients with young age and those who are in low educational status.Verbal information should always be supplement by written information,in all 3 lanuages used in the country.In addition,general public must be educated on safe use of drugs.Futher,oppotunity must be provided to patients to clarify their queries on drugs -prescribed to them,during consultation,dispensing and after leaving the hospitals.